2022
DOI: 10.3892/mco.2022.2523
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of recurrent ovarian cancer with TPM3‑NTRK1 gene rearrangement: A case report

Abstract: NTRK gene fusion is rare in gynecological cancer. Entrectinib is a novel targeted drug, which is a potent inhibitor of TRK A, B and C. The present case report described a case of recurrent ovarian cancer with TPM3-NTRK1 rearrangement, which was detected by next-generation sequencing (NGS) and treated with entrectinib. A 56-year-old woman was diagnosed as having stage IV ovarian cancer with positive pleural fluid cytology. Neoadjuvant chemotherapy and interval debulking surgery, followed by chemotherapy, were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Such excellent clinical efficacy seems to be consistent with a pooled analysis of phase I/II trials of entrectinib and larotrectinib in SGMs 7,9 . However, previous case reports on entrectinib have mainly focused on ovarian cancer, 10 pediatric high‐grade glioma 11,12 soft tissue tumors, neuroendocrine tumor, 13 pancreatic cancer, glioneuronal tumor, 14 and NSCLC 15 . Thus, precise case‐by‐case information on the efficacy of entrectinib for SGMs is limited.…”
Section: Discussionsupporting
confidence: 59%
“…Such excellent clinical efficacy seems to be consistent with a pooled analysis of phase I/II trials of entrectinib and larotrectinib in SGMs 7,9 . However, previous case reports on entrectinib have mainly focused on ovarian cancer, 10 pediatric high‐grade glioma 11,12 soft tissue tumors, neuroendocrine tumor, 13 pancreatic cancer, glioneuronal tumor, 14 and NSCLC 15 . Thus, precise case‐by‐case information on the efficacy of entrectinib for SGMs is limited.…”
Section: Discussionsupporting
confidence: 59%
“…This case demonstrates the promise of Entrectinib in treatment-resistant ovarian cancers harboring an NTRK gene fusion. To our knowledge, only one previous case has reported the use of Entrectinib in any category of ovarian cancer ( Endo et al, 2022 ). Entrectinib was, in that case, ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Entrectinib was, in that case, ineffective. The lack of response suggests the possibility of a false-positive genetic screening, or that NTRK rearrangements may not always be constitutively expressed ( Endo et al, 2022 ). What we believe to be the first report of successful treatment of mucinous ovarian cancer with an NTRK3 fusion with Entrectinib in our case displays the importance of next generation sequencing, especially in patients experiencing disease progression, intolerability of treatment, or tumor resistance to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216], Kušíková et al [217], Decharatchakul et al [218], Ahmed et al [219], Merklinger et al [220], Lei et al [146], Liu et al [221], Chen et al [222], Tan et al [223], Shi et al [224], Ikonnikova et al [225], Shimodaira et al [226], Pravenec et al [227], Zhang et al [228], Shah et al [229], Cicekliyurt and Dermenci [230], Ong et al [98], Nowzari et al [163], Kim et al [231], Bonafiglia et al [232], Selle et al [233],Yoo et al [234], Kasacka et al [235], Wang et al [236], Huang et al [237], Caceres et al [238], Lei et al [239], Lu et al [240], Cui et al [241], Xiao et al [242], Hiramatsu et al [243], Oliver et al [244], Grabowski et al [245], Zhu et al [246] and Li et al [247] demonstrated that the altered expression of CASP1, EDNRA (endothelin receptor type A), F2RL1, FOXP3, TIMP4, CD74, PLK1, TGFB1, GATA6, IRF7, IRF9, BGN (biglycan), CACNA1H, FBLN2, L3MBTL4, COL1A1, POSTN (periostin), THBS4, VARS2, SOD3, ADAMTS13, FBLN5, CYGB (cytoglobin), MST1, GGT7, FGF10, CES1, CYP19A1, CD36, AQP5, ARG1, OXTR (oxytocin receptor), F11R, LEPR (leptin receptor), CDH13, DDR1, FOXO1, PAM (peptidylglycine alpha-amidating monooxygenase), S100A6, B2M, TCF4, VAMP3, GNA14, KLKB1, BDKRB1, SDC3, NFAT5, GRK3, CPXM2, EPHX2 and RCN2 are associated with hypertension. A previous study reported that CASP1 [248], EPHA5 [249], NTRK1 [250], PTN (pleiotrophin) [251], FOXP3 [252], DEF6 [253], TIMP4 [254], SOCS1 [255], CDC20 […”
Section: Discussionmentioning
confidence: 99%